Brain Activity (fNIRS) in Control State Differs from the Execution and Observation of Object-Related and Object-Unrelated Actions. Issue 4 (3rd July 2016) - Balconi, Michela; Cortesi, Livia
ABSTRACT: The authors explored cortical correlates of action execution and observation, directly comparing control condition condition and execution–observation, using functional near-infrared spectroscopy. Transitive actions (meaningful gestures produced in presence of an object) or intransitive actions (meaningful gestures produced in absence of an object) were performed. Increased oxygenated hemoglobin levels were revealed for both action execution and action observation in premotor cortex, and sensorimotor cortex compared to control condition. However, a higher activity in motor areas was observed for action execution than motor observation. In contrast the posterior parietal cortex was similarly activated in case of both execution and observation task. Finally, it was shown that action execution and observation of transitive more than intransitive gestures was supported by similar parietal posterior areas. These findings support the hypothesis of a partial common network for observation and execution of action, and significant implications related to action types (transitive vs. intransitive).